2013
DOI: 10.1021/ja401835j
|View full text |Cite
|
Sign up to set email alerts
|

p-Stilbazole Moieties As Artificial Base Pairs for Photo-Cross-Linking of DNA Duplex

Abstract: In this study, we report a photo-cross-linking reaction between p-stilbazole moieties. p-Stilbazoles were introduced into base-paring positions of complementary DNA strands. The [2 + 2] photocycloaddition reaction occurred rapidly upon light irradiation at 340 nm. Consequently, duplex was cross-linked and highly stabilized after 3 min irradiation. The CD spectrum of the cross-linked duplex indicated that the B-form double-helical structure was not severely distorted. NMR analysis revealed only one conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 39 publications
0
49
0
Order By: Relevance
“…[6] For example, p-stilbazole, [12] coumarin, [13] psoralen, [14] and 3-cyanovinylcarbazole analogues [15] have been reportedt of orm DNA cross-links with pyrimidine nucleotides through[ 2 + +2] photocycloaddition. In general,t hree major mechanisms have been identified for the photoinduced DNA cross-linking process.T hese are photocycloaddition, alkylation via quinone methides( QMs), or alkylation via carbocations.…”
Section: Introductionmentioning
confidence: 99%
“…[6] For example, p-stilbazole, [12] coumarin, [13] psoralen, [14] and 3-cyanovinylcarbazole analogues [15] have been reportedt of orm DNA cross-links with pyrimidine nucleotides through[ 2 + +2] photocycloaddition. In general,t hree major mechanisms have been identified for the photoinduced DNA cross-linking process.T hese are photocycloaddition, alkylation via quinone methides( QMs), or alkylation via carbocations.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant amount of space is required for its photoisomerization because rotation of the benzene ring is involved by breaking the CC π bond and then rotating the CC σ bond . It is confirmed that photoisomerization of stilbene would not happen when it is intercalated in a double‐stranded DNA . Upon UV light irradiation (e.g., 300–400 nm), spiroyran was switched from a closed, nonplanar form into an open, planar merocyanine form with highly π‐conjugated system.…”
Section: Design Of Photoresponsive Self‐assembled Dna Nanomaterials Vmentioning
confidence: 87%
“…Moreover, a number of photosensitive analogues efficiently form crosslink products with dT or dC by [2+2] cycloaddition reaction upon photo irradiation at wavelengths >300 nm. Many of them showed photoreversibility, such as psoralen, azobenzene, p ‐stilbazole, 3‐cyanovinylcarbazole, and others. The DNA crosslinking adducts formed with these compounds can be cleaved into single‐stranded DNA upon photo irradiation at different wavelengths.…”
Section: Introductionmentioning
confidence: 99%